Bias vs. bias : how Fox News anchors discussed Pope Francis’ stance on climate change - Tandoc, Edson C., Jr. (2020)
When Pope Francis, the leader of the Roman Catholic Church, released his encyclical on climate change in June 2015, the Fox News Channel, the most watched cable news network in the United States, faced a dilemma. Some of its news anchors and regular commentators are Catholics, and therefore have a positive bias for the Pope. But the network is also known for its bias against man-made climate change. Guided by cognitive dissonance theory, this study analyzed how Fox News’ anchors and commentators discussed Pope Francis’ stance on climate change. The analysis found a clear ambivalence in their discourse and identified four discursive strategies that they used to navigate discursive dissonance.